2018
DOI: 10.1159/000492525
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Primary Cutaneous Basal Cell Carcinosarcoma

Abstract: A 94-year-old man consulted our hospital due to a rapidly growing tumor on the left cheek. The histological diagnosis of the tumor was basal cell carcinosarcoma, which was composed of intermingled epithelial and mesenchymal components. The former was basal cell carcinoma, while the latter was spindle cell sarcoma. The tumor was completely resected with a 3-mm margin and the patient remained free of local recurrence or distinct metastasis for 2 years. We report here a case of cutaneous basal cell carcinosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Suzuki et al . published a review of 94 cases of CCS between 1972 and 2016, and showed a 4.3% recurrence and metastatic rate for BCCS 6 . This case highlights the potential for aggressive clinical behaviour, recurrence and metastasis despite having definitive Mohs micrographic surgery as the initial treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Suzuki et al . published a review of 94 cases of CCS between 1972 and 2016, and showed a 4.3% recurrence and metastatic rate for BCCS 6 . This case highlights the potential for aggressive clinical behaviour, recurrence and metastasis despite having definitive Mohs micrographic surgery as the initial treatment.…”
Section: Discussionmentioning
confidence: 81%
“…As previously reported, carcinosarcomas may present in various shapes and sizes; therefore, management depends on clinical and histological features [8]. There has been no consensus on definitive margins for excision for cutaneous primary manifestations, as reports describe a range from 0.5-3.5 cm margins [5,9,19,20]. As these defects can be large and in a prominently visible location, it is important for dermatologists to consider referral to plastic surgery for adequate reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and molecular evidences too favor it, with overlapping molecular changes common in both tumor components including P63 and PTCH1 mutations (P63 indicating epithelial derivation of metaplastic carcinomas and a mutation in the PTCH1 gene in the hedgehog pathway in BCC PCCS). [ 7 8 9 10 ] Other hypotheses are: origin from two separate progenitor cells (multiclonal/collision/convergence hypothesis) leading to a collision tumor of two unique neoplasms,[ 1 ] and the composition hypothesis proposing the mesenchymal component as a pseudosarcomatous reaction to the epithelial malignancy. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%